PENGARUH LATIHAN PERMAINAN BOLA BASKET, FUTSAL DAN MOTIVASI BERPRESTASI TERHADAP KEBUGARAN JASMANI - Rohendi, Aep; Budiman, Ali (STKIP Pasundan, 2019)
This study aims to know the game of basketball, Futsal  and motivation of the creation was who were high performing against health condition in SMAN 1 Parongpong. The Methods used to uncover this problem is the experimental methods with the design factorial  2 x 2.  The sample using Cluster Random Sampling, the number of samples from 40 students. The Data using analysis of variance (ANOVA) and next exercise used test tukey. The study concluded that: (1), overall training with a basketball game better than futsal exercises the games for health condition student SMAN 1 Parongpong. (2) there is interaction between the big ball of achievement and motivation to, health condition (3) for learners who have high motivation, high achievers training with a basketball game better than with exercises futsal game against health condition student sman 1, lembang (4) for learners who have high motivation, low achievers there is no significant difference between training with a basketball game and exercise futsal game against student SMAN 1 Parongpong health condition. In other words the ability to their students could increase after these exercises, a basketball game futsal and motivation of students.Healthy  condition.